Digital Forensics and Cyber Crime Second International ICST Conference, ICDF2C 2010, Abu Dhabi, United Arab Emirates, October 4-6, 2010, Revised Selected Papers - Baggili, Ibrahim; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book contains a selection of thoroughly refereed and revised papers from the Second International ICST Conference on Digital Forensics and Cyber Crime, ICDF2C 2010, held October 4-6, 2010 in Abu Dhabi, United Arab Emirates. The field of digital forensics is becoming increasingly important for law enforcement, network security, and information assurance. It is a multidisciplinary area that encompasses a number of fields, including law, computer science, finance, networking, data mining, and criminal justice. The 14 papers in this volume descibe the various applications of this technology and cover a wide range of topics including law enforcement, disaster recovery, accounting frauds, homeland security, and information warfare.
Keywords: Computer science; Computer Communication Networks; Computer vision; Computers -- Law and legislation; Information Systems; Bioinformatics; Computer Science; Legal Aspects of Computing; Management of Computing and Information Systems; Computers and Society; Image Processing and Computer Vision; Bioinformatics; Computer Communication Networks